Study on the difference in cardiopulmonary endurance between different genders and traditional Chinese medicine constitutions - ZHU Limei; LIN Jia; WU Xiaoxu; WANG Kewen; ZHONG Wenliang (Yixue xinzhi zazhi)
Objective To explore the differences in cardiopulmonary endurance between different genders and constitutions based on the constitution theory of traditional Chinese medicine.Methods Standardized training students at Nanping People's Hospital from July 2023 to April 2024 were selected to evaluate the constitution of traditional Chinese medicine and carry out cardiopulmonary exercise tests. Differences in VO2peak and other indicators among different genders and constitutions were analyzed.Results A total of 67 students were included, among which 20 were males (29.85%) and 47 were females (70.15%). There were 21 cases (31.34%) of balanced constitution and 46 cases (68.66%) of biased constitution. The VO2peak of male students [1.97(1.68, 2.27)] was higher than that of female students [1.38(1.17, 1.52)], and the difference was statistically significant (P0.05). The VO2peak of male and female students in the biased constitution group was higher than that of the balanced constitution group, but the difference was not statistically significant (P>0.05). Among different types of biased constitution, VO2peak of phlegm-dampness constitution and damp-heat constitution were higher.Conclusion The traditional Chinese medicine constitution of the students is mainly biased, and there are differences in VO2peak between different genders. The VO2peak value of the gentleness students is higher than that of the biased  students.